2008
DOI: 10.4138/6506
|View full text |Cite
|
Sign up to set email alerts
|

The last 100 million years on the Scotian Margin, offshore eastern Canada: an event-stratigraphic scheme emphasizing biostratigraphic data

Abstract: In order to provide a detailed stratigraphic framework for the Late Cretaceous and Cenozoic basin fill of the Scotian Margin (the continental shelf and continental slope off Nova Scotia, eastern Canada), we have developed an eventbiostratigraphic scheme based mainly on new analyses of several exploration wells. They include Demascota G-32, Hesper I-52, Onondaga E-84 and Wenonah J-75 on the continental shelf, as well as Shelburne G-29 and Shubenacadie H-100 on the continental slope. Several microfossil groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…2) (Wade and MacLean, 1990;Fensome et al, 2008). Due to a paucity of data, formations along the deep water Scotian margin are not formalized and no detailed lithostratigraphic summary exists.…”
Section: Geological Setting Of Study Areamentioning
confidence: 98%
“…2) (Wade and MacLean, 1990;Fensome et al, 2008). Due to a paucity of data, formations along the deep water Scotian margin are not formalized and no detailed lithostratigraphic summary exists.…”
Section: Geological Setting Of Study Areamentioning
confidence: 98%
“…4), both species might be of some importance to constrain the Middle to Late Miocene boundary in deposits off East Greenland, and may help to further refine the biostratigraphic framework in order to address the evolution of the Greenland ice sheet in more detail. Fensome et al, 2008;Schreck et al, 2012), and Batiacasphaera bergenensis sp. nov. and Lavradosphaera elongata sp.…”
Section: Resultsmentioning
confidence: 99%
“…One of us spent several years analyzing Late Cretaceous and Cenozoic assemblages from the Scotian Basin, offshore eastern Canada (Fensome et al 2008(Fensome et al , 2009. Wetzelielloids are relatively common in many assemblages from Paleogene strata in the Scotian Basin, but it was puzzling that specimens with a clearly "popped-out" epeliform archaeopyle like those in Williams and Downie's (1966) classic wetzelielloid study were rarely if ever observed; all Scotian Basin wetzelielloids showed a soleiform archaeopyle or no clearly evident archaeopyle.…”
Section: Page3mentioning
confidence: 99%